Fluorine coating melt-extruded on surface of polyimide film and preparation method thereof

By using melt extrusion technology to prepare the fluorine coating on the surface of the polyimide film, the problem of insufficient water resistance of the film is solved, and the effect of significantly improving water resistance and corrosion resistance is achieved.

CN119842312AInactive Publication Date: 2025-04-18DONGYING LINFU TRADING CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510114570.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Polyimide films have insufficient water resistance during use and need to improve their water properties.

Method used

Fluorine coatings are prepared on the surface of polyimide films using melt extrusion technology, and mixed and reacted with components A (including hydroxytripyridine and hydroxyfluorocarbon resins) and component B (capped prepolymers) and fluoropolymers to form a fluorine-containing polyurethane coating.

Benefits of technology

The water resistance and corrosion resistance of the polyimide film are significantly improved, and its performance in high temperature and humidity environments is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005257824550000091
    Figure BDA0005257824550000091
Patent Text Reader

Abstract

The invention discloses a fluorine coating melt-extruded on the surface of a polyimide film and a preparation method of the fluorine coating, and relates to the technical field of coating materials. The fluorine coating melt-extruded on the surface of the polyimide film is prepared by melt-mixing a component A, a component B and a fluorine-containing polymer, melt-extruding and coating the mixture on the surface of the polyimide film, the component A is a hydroxyl mixture, and the component B is an end-capped prepolymer; the hydroxyl mixture comprises hydroxyl terpyridine and hydroxyl fluorocarbon resin, the hydroxyl terpyridine is prepared by reacting diacetylpyridine with 3, 4-dihydroxyethoxy benzaldehyde, the 3, 4-dihydroxyethoxy benzaldehyde is prepared by reacting 3, 4-dihydroxybenzaldehyde with 2-chloroethanol, and the hydroxyl fluorocarbon resin is prepared by reacting 3, 4-dihydroxybenzaldehyde with 2-chloroethanol. The hydroxyl fluorocarbon resin is prepared by reacting butyl acrylate, hexafluorobutyl acrylate, dodecafluoroheptyl methacrylate, methacrylic acid and 2-hydroxyethyl methacrylate; the fluorine-containing polymer is prepared by carrying out a reaction on p-aminobiphenyl, 2, 3, 5, 6-tetrafluoroterephthalaldehyde and sodium triacetoxyborohydride, and the p-aminobiphenyl is prepared by carrying out a reaction on decafluorobiphenyl and 4-aminophenol; and the water resistance of the polyimide film coated with the fluorine coating is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coating materials, in particular to a fluorine coating melt-extruded on the surface of a polyimide film and a preparation method thereof. Background Art

[0002] Fluorine is mainly used in industrial wires and cables, atomic reactor cables, vehicle wires and parts, industrial coatings and other fields. Polyimide film is used as a polymer. It can self-extinguish when burned. It has high shear mechanical strength and the best low-temperature impact resistance among existing fluoroplastics. It can have high impact strength from room temperature to -260℃, stable chemical properties, good electrical insulation and radiation resistance.

[0003] Although the polyimide film exhibits excellent performance during use, its water resistance still needs to be improved during use. Therefore, the present invention studies and prepares a fluorine coating that is melt-extruded on the surface of the polyimide film to solve this problem. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a fluorine coating melt-extruded on the surface of a polyimide film and a preparation method thereof.

[0005] The present invention proposes a technical solution to solve the above technical problems: a fluorine coating melt-extruded on the surface of a polyimide film, wherein the component A comprises hydroxy terpyridine and a hydroxy fluorocarbon resin; the component B is a capped prepolymer; and the hydroxy terpyridine is prepared by the reaction of diacetylpyridine and 3,4-dihydroxyethoxybenzaldehyde.

[0006] Preferably, the 3,4-dihydroxyethoxybenzaldehyde is obtained by reacting 3,4-dihydroxybenzaldehyde with 2-chloroethanol; the hydroxy fluorocarbon resin is obtained by reacting butyl acrylate, hexafluorobutyl acrylate, dodecafluoroheptyl methacrylate, methacrylic acid and 2-hydroxyethyl methacrylate; and the blocked prepolymer is obtained by reacting benzoyl chloride with diphenylmethane diisocyanate.

[0007] Preferably, the fluorine-containing polymer is prepared by the reaction of p-aminobiphenyl, 2,3,5,6-tetrafluoroterephthalaldehyde and sodium triacetoxyborohydride; and the p-aminobiphenyl is prepared by the reaction of decafluorobiphenyl and 4-aminophenol.

[0008] Preferably, the fluorine-containing polymer is one or a mixture of polytetrafluoroethylene, polyperfluoroethylene propylene, soluble polytetrafluoroethylene, and ethylene-tetrafluoroethylene copolymer.

[0009] Preferably, the method for preparing the fluorine coating melted on the surface of the polyimide film comprises the following specific steps:

[0010] S1. Sodium hydroxide and deionized water are mixed at a mass ratio of 0.8 to 1:30, stirred evenly, and placed in an ice bath, diacetylpyridine in an amount of 0.28 to 0.32 times the mass of sodium hydroxide and 3,4-dihydroxyethoxybenzaldehyde in an amount of 0.22 to 0.24 times the mass of sodium hydroxide are added, and the mixture is kept warm for reaction for 2 to 3 hours, and ammonia water in an amount of 26 to 28 times the mass of sodium hydroxide and having a mass fraction of 20 to 30% is added, and the reaction is continued under reflux for 2 to 3 hours, filtered, and recrystallized with anhydrous ethanol to obtain hydroxyterpyridine;

[0011] S2. The polytetrahydrofuran ether glycol, hydroxy terpyridine, hydroxy fluorocarbon resin, castor oil, 301 catalyst and dibutyltin dilaurate were mixed in a mass ratio of 8 to 10: 0.2 to 0.04: 0.1: 1: 0.02: 0.01, and stirred at room temperature and 2000 to 3000 rpm for 4 to 6 minutes to obtain component A;

[0012] S3. The mixed solution was heated to 120-130°C, vacuum-dehydrated, and then 0.01-0.02 times the mass of the mixed solution of benzoyl chloride and 2-2.4 times the mass of the mixed solution of diphenylmethane diisocyanate were added, and the temperature was raised to 70-80°C, and then stirred at 300-600rpm for 10-20min, and then 50-80 times the mass of benzoyl chloride was added to the mixed solution, and the reaction was continued by stirring for 2-4h, and cooled to room temperature to obtain a capped prepolymer, which is component B;

[0013] S4. p-aminobiphenyl, anhydrous ethanol, 2,3,5,6-tetrafluoroterephthalaldehyde and sodium triacetoxyborohydride are mixed in a mass ratio of 0.3-0.4:100-200:0.4:2, stirred evenly, heated to 76-80° C., refluxed for 2-6 hours, and vacuum filtered to obtain a fluorine-containing polymer;

[0014] S5. Mix component A, component B and fluorine-containing polymer, stir at room temperature and 2000-300 rpm for 1-2 minutes, heat to 210-220°C, quickly pour on the surface of polyimide film, apply with a roller, and finally place at 100-120°C for high temperature aging for 10-30 minutes to obtain a fluorine coating melt-extruded on the surface of the polyimide film.

[0015] Preferably, in the above step S1., the preparation method of amino microsilicon is: mix microsilicon, L3-aminopropyltriethoxysilane and toluene in a mass ratio of 0.1-0.2:1:10, heat to 75-85°C, reflux for 10-12h, filter and wash with ethanol 3-5 times to obtain amino microsilicon.

[0016] Preferably, in the above step S1., the preparation method of 3,4-dihydroxyethoxybenzaldehyde is: 2-chloroethanol and n-butanol are mixed in a mass ratio of 0.8 to 1.2:3, and after stirring evenly, a 3,4-dihydroxybenzaldehyde mixed solution with a mass of 4 to 6 times that of 2-chloroethanol is added dropwise at a rate of 1 to 3 ml / min, wherein the mass ratio of 3,4-dihydroxybenzaldehyde, sodium hydroxide, n-butanol and deionized water in the 3,4-dihydroxybenzaldehyde mixed solution is 3:2:40 to 50:5, reflux reaction is carried out for 10 to 12 hours, vacuum distillation is performed, and purification is performed by column chromatography using ethyl acetate as an eluent to obtain 3,4-dihydroxyethoxybenzaldehyde.

[0017] Preferably, in the above step S2., the preparation method of the hydroxy fluorocarbon resin is: heating ethylene glycol butyl ether to 115-125° C., adding a monomer mixture of 2-4 times the mass of ethylene glycol butyl ether at a rate of 1-3 ml / min, wherein the mass ratio of methyl methacrylate, butyl acrylate, hexafluorobutyl acrylate, dodecafluoroheptyl methacrylate, methacrylic acid, 2-hydroxyethyl methacrylate and ammonium persulfate in the monomer mixture is 2:4:0.5-0.6:2:4:0.01, and after keeping the reaction warm for 2-4 hours, adding sodium hydroxide to adjust the pH to 6.8-7.2 to obtain the hydroxy fluorocarbon resin.

[0018] Preferably, in the above step S3., the mass ratio of polytetrahydrofuran ether glycol to castor oil in the mixed solution is 20 to 30:3.

[0019] Preferably, in the above step S3., the preparation method of p-aminobiphenyl is: decafluorobiphenyl, 4-aminophenol, cesium carbonate and N,N-dimethylformamide are mixed in a mass ratio of 14-16:10:25:100-200, heated to 115-125°C, reacted for 12-14h, cooled to room temperature, added N,N-dimethylformamide and methyl tert-butyl ether in an equal volume, stirred evenly, washed with saturated sodium bicarbonate solution and saturated sodium chloride solution 3-5 times in sequence, dried with anhydrous sodium sulfate, and finally concentrated in vacuo and purified by column chromatography, the eluent being petroleum ether and ethyl acetate in a volume ratio of 3:1, to obtain p-aminobiphenyl.

[0020] Preferably, in the above step S5., the mass ratio of component A, component B and fluorine-containing polymer is 0.8-1.2:1:0.1-0.3; and the thickness of the fluorine coating melt-extruded on the surface of the polyimide film is 4-800 μm.

[0021] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0022] The fluorine coating melt-extruded on the surface of the polyimide film in the present invention is prepared by melt-mixing component A, component B and a fluorine-containing polymer and coating the mixture on the surface of the polyimide film, wherein component A is a hydroxyl mixture and component B is a capped prepolymer.

[0023] The hydroxy mixture includes hydroxy terpyridine and hydroxy fluorocarbon resin. Hydroxy terpyridine is prepared by the reaction of diacetylpyridine and 3,4-dihydroxyethoxybenzaldehyde. 3,4-dihydroxyethoxybenzaldehyde is prepared by the reaction of 3,4-dihydroxybenzaldehyde and 2-chloroethanol. Hydroxy fluorocarbon resin is prepared by the reaction of butyl acrylate, hexafluorobutyl acrylate, dodecafluoroheptyl methacrylate, methacrylic acid and 2-hydroxyethyl methacrylate. The hydroxy terpyridine and the hydroxy fluorocarbon resin are mixed, and the hydroxy fluorocarbon resin containing fluorinated hydrocarbon side chains and the hydroxy terpyridine are formed into a cross-linked network structure, which is then reacted with component B, and a fluorine-containing polymer is introduced to form a fluorine-containing polyurethane fluorine coating, which is melted on the surface of the polyimide film to enhance water resistance and corrosion resistance.

[0024] The fluorine-containing polymer is prepared by the reaction of p-aminobiphenyl, 2,3,5,6-tetrafluoroterephthalaldehyde and sodium triacetoxyborohydride. p-aminobiphenyl is prepared by the reaction of decafluorobiphenyl and 4-aminophenol. The p-aminobiphenyl prepared by the reaction of decafluorobiphenyl and 4-aminophenol has double-terminal amino groups and introduces a large amount of fluorine. The fluorine-containing polymer formed by the reaction of p-aminobiphenyl, 2,3,5,6-tetrafluoroterephthalaldehyde and sodium triacetoxyborohydride has a rough surface and is adsorbent. After being mixed with component A and component B, the fluorine-containing polymer is introduced into the formed polyurethane to ensure the water resistance and corrosion resistance of the polyimide film after coating with the fluorine coating. DETAILED DESCRIPTION

[0025] The present invention is described in detail below by way of examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments to the present invention based on the above content of the present invention. Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art.

[0026] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the fluorine coating prepared by melt extrusion on the surface of the polyimide film in the examples and comparative examples as follows:

[0027] Water resistance: The polyimide film with a fluorine coating melt-extruded on the surface of the polyimide film prepared in the examples and comparative examples was tested for water permeability with reference to GB1037-88. The thickness of the polyimide film with a fluorine coating melt-extruded on the surface of the polyimide film prepared in the examples and comparative examples was 50 μm.

[0028] Corrosion resistance: The polyimide film having a fluorine coating melt-extruded on the surface of the polyimide film prepared in the same embodiment and comparative example was placed in a 10% by mass sulfuric acid solution, and the tensile strength before and after standing was measured with reference to GB / T1040.

[0029] Example 1

[0030] The preparation method of the fluorine coating melt-extruded on the surface of the polyimide film in this embodiment is:

[0031] S1. 2-chloroethanol and n-butanol are mixed in a mass ratio of 0.8 to 1.2:3, stirred evenly, and then a 3,4-dihydroxybenzaldehyde mixed solution with a mass of 4 to 6 times that of 2-chloroethanol is added dropwise at a rate of 1 to 3 ml / min. In the 3,4-dihydroxybenzaldehyde mixed solution, the mass ratio of 3,4-dihydroxybenzaldehyde, sodium hydroxide, n-butanol and deionized water is 3:2:40 to 50:5. The mixture is refluxed for 10 to 12 hours, distilled under reduced pressure, and purified by column chromatography using ethyl acetate as the eluent to obtain 3,4- Dihydroxyethoxybenzaldehyde; sodium hydroxide and deionized water are mixed at a mass ratio of 0.8 to 1:30, stirred evenly and placed in an ice bath, diacetylpyridine in an amount of 0.28 to 0.32 times the mass of sodium hydroxide and 3,4-dihydroxyethoxybenzaldehyde in an amount of 0.22 to 0.24 times the mass of sodium hydroxide are added, the reaction is kept warm for 2 to 3 hours, ammonia water in an amount of 26 to 28 times the mass of sodium hydroxide and having a mass fraction of 20 to 30% is added, the reaction is continued under reflux for 2 to 3 hours, filtered and recrystallized with anhydrous ethanol to obtain hydroxy terpyridine;

[0032] S2. The ethylene glycol butyl ether is heated to 115-125° C., and a monomer mixture of 2-4 times the mass of the ethylene glycol butyl ether is added dropwise at a rate of 1-3 ml / min, wherein the mass ratio of methyl methacrylate, butyl acrylate, hexafluorobutyl acrylate, dodecafluoroheptyl methacrylate, methacrylic acid, 2-hydroxyethyl methacrylate and ammonium persulfate in the monomer mixture is 2:4:0.5-0.6:2:4:0.01, and after the reaction is kept warm for 2-4 hours, sodium hydroxide is added to adjust the pH to 6.8-7.2 to obtain a hydroxy fluorocarbon resin; polytetrahydrofuran ether diol, hydroxy terpyridine, hydroxy fluorocarbon resin, castor oil, 301 catalyst and dibutyltin dilaurate are mixed in a mass ratio of 8-10:0.2-0.04:0.1:1:0.02:0.01, and stirred at room temperature and 2000-3000 rpm for 4-6 minutes to obtain component A;

[0033] S3. The mixed solution was heated to 120-130° C., the mass ratio of polytetrahydrofuran ether glycol to castor oil in the mixed solution was 20-30:3, vacuum dehydration was performed, and then 0.01-0.02 times the mass of the mixed solution and 2-2.4 times the mass of diphenylmethane diisocyanate were added, the mixture was heated to 70-80° C., and then stirred at 300-600 rpm for 10-20 min, and then 50-80 times the mass of benzoyl chloride was added to the mixed solution, the reaction was continued with stirring for 2-4 h, and the mixture was cooled to room temperature to obtain a capped prepolymer, which was component B;

[0034] S4. Decafluorobiphenyl, 4-aminophenol, cesium carbonate and N,N-dimethylformamide are mixed in a mass ratio of 14-16:10:25:100-200, heated to 115-125°C, reacted for 12-14 hours, cooled to room temperature, added with an equal volume of methyl tert-butyl ether of N,N-dimethylformamide, stirred evenly, washed with saturated sodium bicarbonate solution and saturated sodium chloride solution 3-5 times in sequence, dried with anhydrous sodium sulfate, finally concentrated in vacuo and purified by column chromatography, the eluent being petroleum ether and ethyl acetate in a volume ratio of 3:1, to obtain p-aminobiphenyl; p-aminobiphenyl, anhydrous ethanol, 2,3,5,6-tetrafluoroterephthalaldehyde and sodium triacetoxyborohydride are mixed in a mass ratio of 0.3-0.4:100-200:0.4:2, stirred evenly, heated to 76-80°C, refluxed for 2-6 hours, and vacuum filtered to obtain a fluorine-containing polymer;

[0035] S5. Mix component A, component B and fluorine-containing polymer, stir at room temperature and 2000-300 rpm for 1-2 min, heat to 210-220°C, quickly pour on the surface of polyimide film, apply with a roller, and finally place at 100-120°C for high temperature aging for 10-30 min to obtain a fluorine coating melt-extruded on the surface of polyimide film; the mass ratio of component A, component B and fluorine-containing polymer is 0.8-1.2:1:0.1-0.3; the thickness of the fluorine coating melt-extruded on the surface of polyimide film is 4-8 μm.

[0036] Example 2

[0037] The preparation method of the fluorine coating melt-extruded on the surface of the polyimide film in this embodiment is:

[0038] S1. 2-chloroethanol and n-butanol are mixed in a mass ratio of 0.8 to 1.2:3, stirred evenly, and then a 3,4-dihydroxybenzaldehyde mixed solution with a mass of 4 to 6 times that of 2-chloroethanol is added dropwise at a rate of 1 to 3 ml / min. In the 3,4-dihydroxybenzaldehyde mixed solution, the mass ratio of 3,4-dihydroxybenzaldehyde, sodium hydroxide, n-butanol and deionized water is 3:2:40 to 50:5. The mixture is refluxed for 10 to 12 hours, distilled under reduced pressure, and purified by column chromatography using ethyl acetate as the eluent to obtain 3,4- Dihydroxyethoxybenzaldehyde; sodium hydroxide and deionized water are mixed at a mass ratio of 0.8 to 1:30, stirred evenly and placed in an ice bath, diacetylpyridine in an amount of 0.28 to 0.32 times the mass of sodium hydroxide and 3,4-dihydroxyethoxybenzaldehyde in an amount of 0.22 to 0.24 times the mass of sodium hydroxide are added, the reaction is kept warm for 2 to 3 hours, ammonia water in an amount of 26 to 28 times the mass of sodium hydroxide and having a mass fraction of 20 to 30% is added, the reaction is continued under reflux for 2 to 3 hours, filtered and recrystallized with anhydrous ethanol to obtain hydroxy terpyridine;

[0039] S2. The ethylene glycol butyl ether is heated to 115-125° C., and a monomer mixture of 2-4 times the mass of the ethylene glycol butyl ether is added dropwise at a rate of 1-3 ml / min, wherein the mass ratio of methyl methacrylate, butyl acrylate, hexafluorobutyl acrylate, dodecafluoroheptyl methacrylate, methacrylic acid, 2-hydroxyethyl methacrylate and ammonium persulfate in the monomer mixture is 2:4:0.5-0.6:2:4:0.01, and after the reaction is kept warm for 2-4 hours, sodium hydroxide is added to adjust the pH to 6.8-7.2 to obtain a hydroxy fluorocarbon resin; polytetrahydrofuran ether diol, hydroxy terpyridine, hydroxy fluorocarbon resin, castor oil, 301 catalyst and dibutyltin dilaurate are mixed in a mass ratio of 8-10:0.2-0.04:0.1:1:0.02:0.01, and stirred at room temperature and 2000-3000 rpm for 4-6 minutes to obtain component A;

[0040] S3. The mixed solution was heated to 120-130° C., the mass ratio of polytetrahydrofuran ether glycol to castor oil in the mixed solution was 20-30:3, vacuum dehydration was performed, and then 0.01-0.02 times the mass of the mixed solution and 2-2.4 times the mass of diphenylmethane diisocyanate were added, the mixture was heated to 70-80° C., and then stirred at 300-600 rpm for 10-20 min, and then 50-80 times the mass of benzoyl chloride was added to the mixed solution, the reaction was continued with stirring for 2-4 h, and the mixture was cooled to room temperature to obtain a capped prepolymer, which was component B;

[0041] S4. Decafluorobiphenyl, 4-aminophenol, cesium carbonate and N,N-dimethylformamide are mixed in a mass ratio of 14-16:10:25:100-200, heated to 115-125°C, reacted for 12-14 hours, cooled to room temperature, added with an equal volume of methyl tert-butyl ether of N,N-dimethylformamide, stirred evenly, washed with saturated sodium bicarbonate solution and saturated sodium chloride solution 3-5 times in sequence, dried with anhydrous sodium sulfate, finally concentrated in vacuo and purified by column chromatography, the eluent being petroleum ether and ethyl acetate in a volume ratio of 3:1, to obtain p-aminobiphenyl; p-aminobiphenyl, anhydrous ethanol, 2,3,5,6-tetrafluoroterephthalaldehyde and sodium triacetoxyborohydride are mixed in a mass ratio of 0.3-0.4:100-200:0.4:2, stirred evenly, heated to 76-80°C, refluxed for 2-6 hours, and vacuum filtered to obtain a fluorine-containing polymer;

[0042] S5. Mix component A, component B and fluorine-containing polymer, stir at room temperature and 2000-300 rpm for 1-2 min, heat to 210-220°C, quickly pour on the surface of polyimide film, apply with a roller, and finally place at 100-120°C for high temperature aging for 10-30 min to obtain a fluorine coating melted on the surface of polyimide film; the mass ratio of component A, component B and fluorine-containing polymer is 0.8-1.2:1:0.1-0.3; the thickness of the fluorine coating melted on the surface of polyimide film is 4-8 μm.

[0043] Example 3

[0044] The preparation method of the fluorine coating melt-extruded on the surface of the polyimide film in this embodiment is:

[0045] S1. 2-chloroethanol and n-butanol are mixed in a mass ratio of 0.8 to 1.2:3, stirred evenly, and then a 3,4-dihydroxybenzaldehyde mixed solution with a mass of 4 to 6 times that of 2-chloroethanol is added dropwise at a rate of 1 to 3 ml / min. In the 3,4-dihydroxybenzaldehyde mixed solution, the mass ratio of 3,4-dihydroxybenzaldehyde, sodium hydroxide, n-butanol and deionized water is 3:2:40 to 50:5. The mixture is refluxed for 10 to 12 hours, distilled under reduced pressure, and purified by column chromatography using ethyl acetate as the eluent to obtain 3,4- Dihydroxyethoxybenzaldehyde; sodium hydroxide and deionized water are mixed at a mass ratio of 0.8 to 1:30, stirred evenly and placed in an ice bath, diacetylpyridine in an amount of 0.28 to 0.32 times the mass of sodium hydroxide and 3,4-dihydroxyethoxybenzaldehyde in an amount of 0.22 to 0.24 times the mass of sodium hydroxide are added, the reaction is kept warm for 2 to 3 hours, ammonia water in an amount of 26 to 28 times the mass of sodium hydroxide and having a mass fraction of 20 to 30% is added, the reaction is continued under reflux for 2 to 3 hours, filtered and recrystallized with anhydrous ethanol to obtain hydroxy terpyridine;

[0046] S2. The ethylene glycol butyl ether is heated to 115-125° C., and a monomer mixture of 2-4 times the mass of the ethylene glycol butyl ether is added dropwise at a rate of 1-3 ml / min, wherein the mass ratio of methyl methacrylate, butyl acrylate, hexafluorobutyl acrylate, dodecafluoroheptyl methacrylate, methacrylic acid, 2-hydroxyethyl methacrylate and ammonium persulfate in the monomer mixture is 2:4:0.5-0.6:2:4:0.01, and after the reaction is kept warm for 2-4 hours, sodium hydroxide is added to adjust the pH to 6.8-7.2 to obtain a hydroxy fluorocarbon resin; polytetrahydrofuran ether diol, hydroxy terpyridine, hydroxy fluorocarbon resin, castor oil, 301 catalyst and dibutyltin dilaurate are mixed in a mass ratio of 8-10:0.2-0.04:0.1:1:0.02:0.01, and stirred at room temperature and 2000-3000 rpm for 4-6 minutes to obtain component A;

[0047] S3. The mixed solution was heated to 120-130° C., the mass ratio of polytetrahydrofuran ether glycol to castor oil in the mixed solution was 20-30:3, vacuum dehydration was performed, and then 0.01-0.02 times the mass of the mixed solution and 2-2.4 times the mass of diphenylmethane diisocyanate were added, the mixture was heated to 70-80° C., and then stirred at 300-600 rpm for 10-20 min, and then 50-80 times the mass of benzoyl chloride was added to the mixed solution, the reaction was continued with stirring for 2-4 h, and the mixture was cooled to room temperature to obtain a capped prepolymer, which was component B;

[0048] S4. Mix component A, component B and polytetrafluoroethylene, stir at room temperature and 2000-300 rpm for 1-2 minutes, heat to 210-220°C, quickly pour on the surface of the polyimide film, apply with a roller, and finally place at 100-120°C for high temperature aging for 10-30 minutes to obtain a fluorine coating melted on the surface of the polyimide film; the mass ratio of component A, component B and fluorine-containing polymer is 0.8-1.2:1:0.1-0.3; the thickness of the fluorine coating melted on the surface of the polyimide film is 4-8μm.

[0049] Example 4

[0050] The preparation method of the fluorine coating melt-extruded on the surface of the polyimide film in this embodiment is:

[0051] S1. 2-chloroethanol and n-butanol are mixed in a mass ratio of 0.8 to 1.2:3, stirred evenly, and then a 3,4-dihydroxybenzaldehyde mixed solution with a mass of 4 to 6 times that of 2-chloroethanol is added dropwise at a rate of 1 to 3 ml / min. In the 3,4-dihydroxybenzaldehyde mixed solution, the mass ratio of 3,4-dihydroxybenzaldehyde, sodium hydroxide, n-butanol and deionized water is 3:2:40 to 50:5. The mixture is refluxed for 10 to 12 hours, distilled under reduced pressure, and purified by column chromatography using ethyl acetate as the eluent to obtain 3,4- Dihydroxyethoxybenzaldehyde; sodium hydroxide and deionized water are mixed at a mass ratio of 0.8 to 1:30, stirred evenly and placed in an ice bath, diacetylpyridine in an amount of 0.28 to 0.32 times the mass of sodium hydroxide and 3,4-dihydroxyethoxybenzaldehyde in an amount of 0.22 to 0.24 times the mass of sodium hydroxide are added, the reaction is kept warm for 2 to 3 hours, ammonia water in an amount of 26 to 28 times the mass of sodium hydroxide and having a mass fraction of 20 to 30% is added, the reaction is continued under reflux for 2 to 3 hours, filtered and recrystallized with anhydrous ethanol to obtain hydroxy terpyridine;

[0052] S2. The ethylene glycol butyl ether is heated to 115-125° C., and a monomer mixture of 2-4 times the mass of the ethylene glycol butyl ether is added dropwise at a rate of 1-3 ml / min, wherein the mass ratio of methyl methacrylate, butyl acrylate, hexafluorobutyl acrylate, dodecafluoroheptyl methacrylate, methacrylic acid, 2-hydroxyethyl methacrylate and ammonium persulfate in the monomer mixture is 2:4:0.5-0.6:2:4:0.01, and after the reaction is kept warm for 2-4 hours, sodium hydroxide is added to adjust the pH to 6.8-7.2 to obtain a hydroxy fluorocarbon resin; polytetrahydrofuran ether diol, hydroxy terpyridine, hydroxy fluorocarbon resin, castor oil, 301 catalyst and dibutyltin dilaurate are mixed in a mass ratio of 8-10:0.2-0.04:0.1:1:0.02:0.01, and stirred at room temperature and 2000-3000 rpm for 4-6 minutes to obtain component A;

[0053] S3. The mixed solution was heated to 120-130° C., the mass ratio of polytetrahydrofuran ether glycol to castor oil in the mixed solution was 20-30:3, vacuum dehydration was performed, and then 0.01-0.02 times the mass of the mixed solution and 2-2.4 times the mass of diphenylmethane diisocyanate were added, the mixture was heated to 70-80° C., and then stirred at 300-600 rpm for 10-20 min, and then 50-80 times the mass of benzoyl chloride was added to the mixed solution, the reaction was continued with stirring for 2-4 h, and the mixture was cooled to room temperature to obtain a capped prepolymer, which was component B;

[0054] S4. Component A, component B and polyperfluoroethylene propylene are mixed, stirred at room temperature and 2000-300 rpm for 1-2 min, heated to 210-220°C, quickly poured on the surface of the polyimide film, and coated with a roller, and finally placed at 100-120°C for high temperature aging for 10-30 min to obtain a fluorine coating melt-extruded on the surface of the polyimide film; the mass ratio of component A, component B and fluorine-containing polymer is 0.8-1.2:1:0.1-0.3; the thickness of the fluorine coating melted on the surface of the polyimide film is 4-8 μm

[0055] Comparative Example 1

[0056] The preparation method of Comparative Example 1 is the same as that of Example 2. The difference between the fluorine coating melt-extruded on the surface of the polyimide film and Example 2 is that the hydroxyl mixture only includes hydroxy terpyridine.

[0057] Comparative Example 2

[0058] The preparation method of Comparative Example 2 is the same as that of Example 2. The difference between the fluorine coating melt-extruded on the surface of the polyimide film and Example 2 is that the hydroxyl mixture only includes hydroxyl fluorocarbon resin.

[0059] Comparative Example 3

[0060] The preparation method of Comparative Example 3 is the same as that of Example 2. The difference between the fluorine coating melt-extruded on the surface of the polyimide film and Example 2 is that the fluorine-containing polymer is only 2,3,5,6-tetrafluoroterephthalaldehyde.

[0061] Comparative Example 4

[0062] The preparation method of Comparative Example 4 is the same as that of Example 2. The difference between the fluorine coating melt-extruded on the surface of the polyimide film and Example 2 is that the fluorine coating melt-extruded on the surface of the polyimide film is prepared by mixing component A and component B and coating the mixture on the surface of the polyimide film.

[0063] Effect example

[0064] Table 1 below shows the performance analysis results of the fluorine coating melt-extruded on the surface of the polyimide film obtained by using Examples 1 to 4 of the present invention and Comparative Examples 1 to 4:

[0065] Table 1

[0066]

[0067] By comparing the experimental data of the examples and the comparative examples in Table 1, it can be clearly found that the fluorine coating melt-extruded on the surface of the polyimide film prepared by using Examples 1, 2, 3, and 4 has excellent water resistance and corrosion resistance.

[0068] From the comparison of the experimental data of Example 1, Example 2, Example 3, Example 4 and Comparative Example 1, Comparative Example 2, Comparative Example 3, it can be found that by mixing hydroxy terpyridine and hydroxy fluorocarbon resin, the hydroxy fluorocarbon resin containing fluorinated hydrocarbon side chains and hydroxy terpyridine form a cross-linked network structure, which is then reacted with component B, and a fluorine-containing polymer is introduced to form a fluorine-containing polyurethane fluorine coating, which is melt-extruded on the surface of the polyimide film to enhance water resistance.

[0069] From the comparison of the experimental data of Example 1, Example 2, Example 3 and Comparative Example 4, Comparative Example 5, it can be found that the fluorine-containing polymer formed by the reaction of p-aminobiphenyl, 2,3,5,6-tetrafluoroterephthalaldehyde and sodium triacetoxyborohydride, which has a double-terminal amino group and introduces a large amount of fluorine, has a rough surface and is adsorptive. After mixing with component A and component B, the fluorine-containing polymer is introduced into the formed polyurethane to ensure the water resistance of the polyimide film after coating with the fluorine coating.

[0070] Obviously, the above embodiments are merely examples for clearly illustrating the embodiments of the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. However, these obvious changes or modifications derived from the spirit of the present invention are still within the scope of protection of the present invention.

Claims

1. A fluorine coating melt-extruded on the surface of a polyimide film, characterized in that: The invention comprises component A, component B and fluorine-containing polymer; the component A comprises hydroxy terpyridine and hydroxy fluorocarbon resin; the component B is a capped prepolymer; the hydroxy terpyridine is prepared by the reaction of diacetyl pyridine and 3,4-dihydroxyethoxybenzaldehyde.

2. A fluorine coating melt-extruded on the surface of a polyimide film according to claim 1, characterized in that: The 3,4-dihydroxyethoxybenzaldehyde is prepared by the reaction of 3,4-dihydroxybenzaldehyde and 2-chloroethanol; the hydroxy fluorocarbon resin is prepared by the reaction of butyl acrylate, hexafluorobutyl acrylate, dodecafluoroheptyl methacrylate, methacrylic acid and 2-hydroxyethyl methacrylate; and the blocked prepolymer is prepared by the reaction of benzoyl chloride and diphenylmethane diisocyanate.

3. The fluorine coating melt-extruded on the surface of a polyimide film according to claim 1, characterized in that: The fluorine-containing polymer is prepared by the reaction of p-aminobiphenyl, 2,3,5,6-tetrafluoroterephthalaldehyde and sodium triacetoxyborohydride; and the p-aminobiphenyl is prepared by the reaction of decafluorobiphenyl and 4-aminophenol.

4. The fluorine coating melt-extruded on the surface of a polyimide film according to claim 1, characterized in that: The fluorine-containing polymer is one or a mixture of polytetrafluoroethylene, polyperfluoroethylene propylene, soluble polytetrafluoroethylene, and ethylene-tetrafluoroethylene copolymer.

5. A method for preparing a fluorine coating melt-extruded on the surface of a polyimide film as claimed in claim 1, characterized in that: The specific steps include: S1. Sodium hydroxide and deionized water are mixed at a mass ratio of 0.8 to 1:30, stirred evenly, and placed in an ice bath, diacetylpyridine in an amount of 0.28 to 0.32 times the mass of sodium hydroxide and 3,4-dihydroxyethoxybenzaldehyde in an amount of 0.22 to 0.24 times the mass of sodium hydroxide are added, and the mixture is kept warm for reaction for 2 to 3 hours, and ammonia water in an amount of 26 to 28 times the mass of sodium hydroxide and having a mass fraction of 20 to 30% is added, and the reaction is continued under reflux for 2 to 3 hours, filtered, and recrystallized with anhydrous ethanol to obtain hydroxyterpyridine; S2. The polytetrahydrofuran ether glycol, hydroxy terpyridine, hydroxy fluorocarbon resin, castor oil, 301 catalyst and dibutyltin dilaurate were mixed in a mass ratio of 8 to 10: 0.2 to 0.04: 0.1: 1: 0.02: 0.01, and stirred at room temperature and 2000 to 3000 rpm for 4 to 6 minutes to obtain component A; S3. The mixed solution was heated to 120-130°C, vacuum-dehydrated, and then 0.01-0.02 times the mass of the mixed solution of benzoyl chloride and 2-2.4 times the mass of the mixed solution of diphenylmethane diisocyanate were added, and the temperature was raised to 70-80°C, and then stirred at 300-600rpm for 10-20min, and then 50-80 times the mass of benzoyl chloride was added to the mixed solution, and the reaction was continued by stirring for 2-4h, and cooled to room temperature to obtain a capped prepolymer, which is component B; S4. p-aminobiphenyl, anhydrous ethanol, 2,3,5,6-tetrafluoroterephthalaldehyde and sodium triacetoxyborohydride are mixed in a mass ratio of 0.3-0.4:100-200:0.4:2, stirred evenly, heated to 76-80° C., refluxed for 2-6 hours, and vacuum filtered to obtain a fluorine-containing polymer; S5. Mix component A, component B and fluorine-containing polymer, stir at room temperature and 2000-300 rpm for 1-2 minutes, heat to 210-220°C, quickly pour on the surface of polyimide film, apply with a roller, and finally place at 100-120°C for high temperature aging for 10-30 minutes to obtain a fluorine coating melted on the surface of the polyimide film.

6. The method for preparing a fluorine coating melt-extruded on the surface of a polyimide film according to claim 5, characterized in that: In the above step S1., the preparation method of 3,4-dihydroxyethoxybenzaldehyde is as follows: 2-chloroethanol and n-butanol are mixed in a mass ratio of 0.8 to 1.2:3, and after stirring evenly, a 3,4-dihydroxybenzaldehyde mixed solution with a mass of 4 to 6 times that of 2-chloroethanol is added dropwise at a rate of 1 to 3 ml / min, wherein the mass ratio of 3,4-dihydroxybenzaldehyde, sodium hydroxide, n-butanol and deionized water in the 3,4-dihydroxybenzaldehyde mixed solution is 3:2:40 to 50:5, reflux reaction for 10 to 12 hours, distill under reduced pressure, and purify by column chromatography using ethyl acetate as an eluent to obtain 3,4-dihydroxyethoxybenzaldehyde.

7. The method for preparing a fluorine coating melt-extruded on the surface of a polyimide film according to claim 5, characterized in that: In the above step S2., the preparation method of the hydroxy fluorocarbon resin is: heating ethylene glycol butyl ether to 115-125°C, adding a monomer mixture of 2-4 times the mass of ethylene glycol butyl ether at a rate of 1-3 ml / min, wherein the mass ratio of methyl methacrylate, butyl acrylate, hexafluorobutyl acrylate, dodecafluoroheptyl methacrylate, methacrylic acid, 2-hydroxyethyl methacrylate and ammonium persulfate in the monomer mixture is 2:4:0.5-0.6:2:4:0.01, and after keeping the reaction warm for 2-4 hours, adding sodium hydroxide to adjust the pH to 6.8-7.2 to obtain the hydroxy fluorocarbon resin.

8. The method for preparing a fluorine coating melt-extruded on the surface of a polyimide film according to claim 5, characterized in that: In the above step S3., the mass ratio of polytetrahydrofuran ether glycol to castor oil in the mixed solution is 20-30:

3.

9. The method for preparing a fluorine coating melt-extruded on the surface of a polyimide film according to claim 5, characterized in that: In the above step S3., the preparation method of p-aminobiphenyl is: decafluorobiphenyl, 4-aminophenol, cesium carbonate and N,N-dimethylformamide are mixed in a mass ratio of 14-16:10:25:100-200, heated to 115-125°C, reacted for 12-14h, cooled to room temperature, added N,N-dimethylformamide and methyl tert-butyl ether in an equal volume, stirred evenly, washed with saturated sodium bicarbonate solution and saturated sodium chloride solution 3-5 times in sequence, dried with anhydrous sodium sulfate, and finally concentrated in vacuo and purified by column chromatography, the eluent being petroleum ether and ethyl acetate in a volume ratio of 3:1, to obtain p-aminobiphenyl.

10. The method for preparing a fluorine coating melt-extruded on the surface of a polyimide film according to claim 5, characterized in that: In the above step S5., the mass ratio of component A, component B and fluorine-containing polymer is 0.8-1.2:1:0.1-0.3; The thickness of the fluorine coating layer melted on the surface of the polyimide film is 4 to 8 μm.

Citation Information

Cited By

  • High-adhesion electrical insulation polyolefin hot melt adhesive and preparation method thereof

    CN120574539A